The relevance of auditory feedback for consonant production: The case of fricatives. (November 2019) - Klein, Eugen; Brunner, Jana; Hoole, Phil
Highlights: Speakers compensate for real-time auditory shifts during production of fricatives. Speakers able to produce a single fricative with multiple compensatory strategies. Compensatory magnitude increases over the course of the experiment. Acoustic parameters modified in response to perturbation vary across speakers. Compensatory adjustments are degraded under noise-masked auditory feedback. Abstract: Previous perturbation studies of vowels show that speakers employ auditory feedback to monitor their own speech production and adjust their articulation when auditory errors occur. In contrast, although a few studies have demonstrated that acoustic changes may occur to consonants under perturbed or masked auditory feedback, it is less clear if speakers rely on auditory feedback to systematically restore acoustic parameters of their perturbed consonant production. To investigate this question, we conducted a study with Russian speakers in which the spectrum of the fricative [s j ] was perturbed in opposing directions depending on the word the sound was embedded in. Consequently, speakers had to develop two different strategies to successfully produce the fricative. Following the insights of previous descriptive as well as oral-articulatory perturbation studies of fricatives, we employed a multi-parameter analysis where we examined the relevance of a series of acoustic measures for describing the adaptation process. Our findings demonstrate that although all participants reacted to the auditory perturbations, they did so by adjusting a varying set of acoustic parameters. Furthermore, the degree to which each participant was able to develop two coherent production strategies for the two opposing perturbation directions varied considerably. We discuss this adaptation variability in the context of the articulatory-acoustic complexity of fricatives.